2010
DOI: 10.1111/j.1442-2050.2009.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of pathologically involved celiac node metastases in node-positive patients with carcinoma of the distal esophagus or gastroesophageal junction: a surgical series from the Mayo Clinic

Abstract: The management of esophageal cancer with involvement of celiac lymph nodes is controversial. The purpose of this retrospective study was to evaluate the clinical importance of metastases to celiac lymph nodes in patients with carcinoma of the distal esophagus or gastroesophageal junction (GEJ) who undergo surgical treatment with curative intent. We reviewed the medical records of 310 patients who underwent definitive esophagectomy at the Mayo Clinic, Rochester, Minnesota, between 1976 and 1999 for carcinoma of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…9 Total gastrectomy with en-bloc resection of advanced gastric cardiac carcinomas involving the esophagus along with the surrounding lymph nodes in the celiac axis region has been advocated to improve patient survival. 21,23 We found herein that the AJCC 7th system was not as good for prognostic stratification of patients with gastric cardiac carcinomas involving the esophagus when they were grouped as esophageal cancers, compared with when staged as gastric cancers. 8 These results will certainly fuel the ongoing controversy debate about the pathogenesis, origin, and classification of gastroesophageal junction cancers and gastric cardiac carcinomas involving the esophagus.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…9 Total gastrectomy with en-bloc resection of advanced gastric cardiac carcinomas involving the esophagus along with the surrounding lymph nodes in the celiac axis region has been advocated to improve patient survival. 21,23 We found herein that the AJCC 7th system was not as good for prognostic stratification of patients with gastric cardiac carcinomas involving the esophagus when they were grouped as esophageal cancers, compared with when staged as gastric cancers. 8 These results will certainly fuel the ongoing controversy debate about the pathogenesis, origin, and classification of gastroesophageal junction cancers and gastric cardiac carcinomas involving the esophagus.…”
Section: Discussionmentioning
confidence: 88%
“…This rate was similar to that reported in Japanese patients 22 and slightly better than that described in a similar study from Taiwan, in which no long-term survival was observed in patients with celiac nodal diseases. 2 Recently, Schomas et al 23 systematically investigated the prognostic significance of celiac axis nodal involvement in patients with gastroesophageal junction cancer and found that the survival rates of those with celiac nodal metastasis were comparable with those of pN1, and similar to patients with stage pIII disease. However, over 52% of their patients had cancers within the distal esophagus above the gastroesophageal junction; therefore, their data may not be comparable with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Our report showed that the survival rate decreased with an increasing number of metastatic nodes, and that the optimal cutoff value was between 1–6 and ≥ 7 metastatic nodes. On the other hand, there was little evidence supporting that the site of metastatic nodes influenced the prognosis of esophageal carcinoma [14,22,23]. For example, celiac node metastasis, which was regarded as M1 disease in the past, did not mean poor prognosis in node-positive patients with esophageal cancer [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there was little evidence supporting that the site of metastatic nodes influenced the prognosis of esophageal carcinoma [14,22,23]. For example, celiac node metastasis, which was regarded as M1 disease in the past, did not mean poor prognosis in node-positive patients with esophageal cancer [22,23]. It was found that for middle and lower thoracic esophageal carcinoma, survival of patients with celiac node metastasis did not differ from those with left gastric node metastasis [23].…”
Section: Discussionmentioning
confidence: 99%
“…To take into account these risks and the inconclusive clinical studies, neoadjuvant treatment and the following surgery should currently only be carried out for patients in good general condition with advanced but resectable, non-metastatic EC (>cT2 and/or Npos and M0). It should be noted that lymph node metastases at the coeliac trunk (formally M1a) should be treated as regional lymph node metastases [16][17][18][19]. If necessary, staging laparoscopy should be performed to confirm the diagnosis or rule out a peritoneal carcinosis.…”
Section: Initial Diagnostics and Imaging Techniques For Ec Stagingmentioning
confidence: 98%